2011
DOI: 10.1186/1471-2148-11-236
|View full text |Cite
|
Sign up to set email alerts
|

Why small males have big sperm: dimorphic squid sperm linked to alternative mating behaviours

Abstract: BackgroundSperm cells are the target of strong sexual selection that may drive changes in sperm structure and function to maximize fertilisation success. Sperm evolution is regarded to be one of the major consequences of sperm competition in polyandrous species, however it can also be driven by adaptation to the environmental conditions at the site of fertilization. Strong stabilizing selection limits intra-specific variation, and therefore polymorphism, among fertile sperm (eusperm). Here we analyzed reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
2
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 32 publications
1
67
2
13
Order By: Relevance
“…Specifically, these results support findings by Cigliano (1995) and Wada et al (2010) in that some male cephalopods appear to strategically regulate their copulation time based on the mating history of the female, presumably to maximise their reproductive output by balancing both their chance of paternity and their ability to successfully copulate with other females. Sperm competition appears prevalent among cephalopod mating systems (Cigliano, 1995;Hanlon et al, 1999;Naud et al, 2004;Shaw & Sauer, 2004;Wada et al, 2005b;Wada et al, 2006;Buresch et al, 2009;Wada et al, 2010;Iwata et al, 2011;Sato et al, 2013). Future studies using molecular markers might identify correlations between paternity and behavioural patterns including copulation duration and chronology.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, these results support findings by Cigliano (1995) and Wada et al (2010) in that some male cephalopods appear to strategically regulate their copulation time based on the mating history of the female, presumably to maximise their reproductive output by balancing both their chance of paternity and their ability to successfully copulate with other females. Sperm competition appears prevalent among cephalopod mating systems (Cigliano, 1995;Hanlon et al, 1999;Naud et al, 2004;Shaw & Sauer, 2004;Wada et al, 2005b;Wada et al, 2006;Buresch et al, 2009;Wada et al, 2010;Iwata et al, 2011;Sato et al, 2013). Future studies using molecular markers might identify correlations between paternity and behavioural patterns including copulation duration and chronology.…”
Section: Resultsmentioning
confidence: 99%
“…Although a factor that infl uences the male-type decision remains to be identifi ed, this system offers extremely a unique situation where internal and external fertilization coexist within a single spawning episode. Previously, we found that sneaker sperm are ~50 % longer than consort sperm (Iwata et al 2011 ). Although no such clear within-species dimorphic eusperm had been reported previously, there are many examples of sperm size differences among closely related species, which have largely been explained as the consequences of sperm competition (Gage 1994 ;Briskie and Montgomerie 1992 ;Gomendio and Roldan 1991 ).…”
Section: Discussionmentioning
confidence: 79%
“…Despite extended arguments on the evolutionary adaptation of sperm cooperation for reproductive success (Immler 2008 ;Foster and Pizzari 2010 ), little is known about how sperm form functional conjugates (Moore et al 2002 ). Previously, we found that each male of the coastal squid Loligo bleekeri produces one of two types of morphologically distinct euspermatozoa , the two types being linked to distinctly different male mating behaviors (Iwata et al 2011 ). Consort males produce spermatozoa with short fl agella and transfer sperm capsules (spermatophores ) to internal locations of the females, inside the oviduct, whereas sneaker males produce long-fl agellum sperm and transfer spermatophores to the outer body wall of the same females ( Fig.…”
Section: Sperm From Sneaker Males Swarm In Response To Respiratory Comentioning
confidence: 86%
See 2 more Smart Citations